Polymers and the Water Crisis in Brazil: Opportunities for Technological and Environmental Development - Corrêa, Harrison Lourenço (Journal of Research Updates in Polymer Science, 2022)
At a global level, climate changes have been responsible for alterations in rainfall regimes. Numerous impacts resulting from such complex dynamics negatively affect peoples and nations. Desertification, sandification, floods, and droughts are some evident examples of the transformation the world is undergoing. In Brazil, the past few years have been characterized by long periods of drought in some regions. As a result, there have been considerable drops in the levels of reservoirs that supply important urban and economic axes in the country. Implications on the national economy and entire production chains aggravate the current scenario, along with two long years of the Sars-Cov-2 pandemic period. From this perspective, the present work aims to address the pressing need to adopt technologies and techniques for collecting and treating rainwater. To this end, specialized databases were accessed in order to evaluate ongoing research on the use of polymeric materials to achieve that goal.